Bipolar type I diagnosis after a manic episode secondary to SARS-CoV-2 infection: A case report. Issue 31 (5th August 2022) - D'Imperio, Ambra; Lo, Jonathan; Bettini, Luca; Prada, Paco; Bondolfi, Guido
Abstract : Rationale: Our objective is to provide awareness about psychotic vulnerability in patients infected with SARS-CoV-2 and to better understand the role of steroid withdrawal in manic episodes, especially with its common usage in respiratory disease caused by SARS-CoV-2. Patient concerns: We present the case of a patient who was hospitalized twice after discontinuing steroid therapy for SARS-CoV-2 infection and presented with a manic episode despite not having a psychiatric history. Diagnosis: The patient tested positive on a polymerase chain reaction test for SARS-CoV-2 and developed pneumonia. Other organic differential diagnoses such as encephalitis were also investigated and excluded. Manic episodes were diagnosed according to DSM-V criteria. Subsequently, the patient was diagnosed with type I bipolar disorder. Interventions: According to the protocols, supplemental oxygen therapy, prophylactic enoxaparin and intravenous (IV) steroids were administered. Steroid dosage was gradually reduced under supervision. During the acute mania, antipsychotics and benzodiazepines were administered. Outcomes: After discharge, the patient was admitted to the psychiatric consultation service. He first received mood stabilizer therapy and then received supportive psychotherapy. Lessons: Psychotic symptoms commonly occur after the discontinuation of high-dose steroid therapy; however, controlled tapering may prevent these side effects. Only a few cases have reported concomitant SARS-CoV-2 infection and manic episodes, often with an apparent relationship with steroid withdrawal syndrome. In this case, we considered psychotic vulnerability a condition that is often underestimated. In consideration of the SARS-CoV-2 pandemic, the case may represent an underlying trigger for psychotic decompensation, which, in concert with neuroinflammation, may induce a manic episode.